The Influence of Drill Practice And Suspended Ball Practice On The Accuracy of Service In Sila In The Game of Sepak Takraw Among Students of The Bala Keselamatan (BK) Palu High School Extracurricular (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the accuracy of sila service in Extracurricular students of SMA BK Palu. This type of research is quantitative research using experimental methods. The sample of this study was Extracurricular Students at SMA BK Palu totaling 22 students using total sampling technique. This study uses a pretest-posttest design, the results of the initial t-test (pre-test) and final test (post-test) obtained a t-count value in Drill practice of 19.39> 2.228 t-table with a significance level of 0.000 2.228 t-table with a significant level of 0.000